KONSTRUKSI PASIF BAHASA INDONESIA DAN BAHASA MANDARIN - Muslim, Mohammad Umar; Aryanti, Uti (UI Scholars Hub, 2026)
Indonesian and Mandarin Chinese have passive constructions. A systematic comparison of passive constructions in these two languages has not been conducted and is not based on corpus data. In this paper, we will compare passive constructions in these two languages based on word order, verb type, and agent. The data was taken from the Indonesian language corpus LCC (https://cqpweb.lancs.ac.uk) and the Mandarin language corpus BCC (https://bcc.blcu.edu.cn) . The data in this paper consists of passive sentences and other sentences that have the same meaning (synonyms) as passive sentences in Indonesian and Mandarin. From the data analysis, it was concluded that (1) the word order of passive constructions in Indonesian is more flexible than that in Mandarin, (2) static transitive verbs are used more frequently in passive constructions in Indonesian than in Mandarin, (3) agents in Indonesian passive constructions can be preceded by prepositions, while agents in Mandarin passive constructions are not preceded by prepositions, (4) agents in the form of pronouns are found more frequently in Mandarin passive constructions than in Indonesian passive constructions.